The Influence of regional languages on presenting and solving local mathematics problems: a systematic literature review - Safitri, Widya Sani; Sahmin, Sahmin; Isnawan , Muhamad Galang; Indrawati, Indrawati (Nashir Al-Kutub Indonesia, 2024)
This research aims to find out how the use of regional languages ​​influences the presentation and solving of mathematical problems. In conducting research, researchers used the SLR (Systematic Literature Review) research method. Researchers searched journals on several websites with predetermined keywords. To make it easier to filter articles to be researched, researchers used the PRISMA flow. Where, there are several stages, namely identification, screening, eligibility, inclusion and exclusion criteria. In the final stage, 21 articles were obtained for research. The research results showed that the use of regional languages ​​in mathematics learning showed a positive influence on students' attitudes and motivation in learning mathematics. Apart from that, there is an increase in students' understanding of mathematical concepts and it makes it easier for students to solve local mathematics problems.